ENERGY BALANCE AND PERFORMANCE OF BALI CATTLE FED WITH DIFFERENT TYPES AND COMPOSITIONS OF FORAGE - Suryani, N. N.; Mahardika, I G.; Putra, S.; Sujaya, N. (E-Journal of Animal Science Udayana University; Vol 1, No 1, Tahun 2012, 2013)
An experiment was carried out to determine the energy balance and performance of bali cattle fed different forage compositions. Randomized Block Design consisted of four feed treatments with 3 block of weight live as replicates were used in this study. The initial weight of male bali cattle used range between 181-265 kg. These four treatments based on dry matter (DM) were: A (45% elephant grass + 0% rice straw + 15% glyricidia + 10% calliandra + 30% concentrate); B (30% elephant grass +10% rice straw + 20% glyricidia + 10% calliandra+ 30% concentrate) ; C (15% elephant grass +20% rice straw + 25% glyricidia +10% calliandra + 30% concentrate)  and treatmen D (0% elephant grass + 30% rice straw + 30% glyricidia  + 10% calliandra+ 30% concentrate) . Variables which were measured: nutrient consumption, balance energy, energy retention, weight gain and FCR. The results showed that Dry Matter and energy intake were highest in treatment C, but not significantly different (P>0.05) compare with the others. Weight gain was significantly the highest (P<0.05) in treatment C and FCR significantly the lowest (P<0.05). Energy retention treatments B, C and D did not show significant differences (P> 0.05) but in the A treatment significantly the lowest (P<0.05). Heat production significantly the lowest (P<0.05) in treatment D compared to treatment A and C. It could be concluded that the ration C gave lowest FCR and had higest weight gain compared to others treatment.
Keywords: forage composition, energy balance, bali cattle productivity